(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonotic disease, global distributed throughout the horse populations. The control of leptospirosis is often difficult and requires host specific measures, therefore, methods for disease control vary among serovar and, host immunology status.